2017
DOI: 10.1186/s13256-017-1401-5
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous rosacea: a case report

Abstract: BackgroundGranulomatous rosacea is a rare chronic inflammatory skin disease with an unknown origin. The role of Demodex follicularum in its pathogenesis is currently proved.Case presentationWe report a case of a 54-year-old Moroccan man with a 3-month history of erythematous, nonpruritic papules on the lateral side around the eyes. Dermoscopy and histology confirmed the diagnosis of granulomatous rosacea.ConclusionsWe describe another clinical presentation of granulomatous rosacea with a clinical-dermoscopic-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…3 erythematous halo filling the follicular openings were reported in a patient with granulomatous rosacea. 7 These two case reports and one study, which were performed by handheld dermoscope, revealed similar findings. Our study was the first report to use videodermoscope and contains a control group to compare the results with the normal skin without demodicosis.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…3 erythematous halo filling the follicular openings were reported in a patient with granulomatous rosacea. 7 These two case reports and one study, which were performed by handheld dermoscope, revealed similar findings. Our study was the first report to use videodermoscope and contains a control group to compare the results with the normal skin without demodicosis.…”
Section: Discussionsupporting
confidence: 59%
“…3 Two different case reports with secondary demodicosis and with granulomatous rosacea confirmed the Demodex tails as a specific feature. 6,7 We documented them in all patients with demodicosis. Thus, we noticed Demodex tails as the major videodermoscopic finding and the only specific and sensitive criteria for the diagnosis.…”
Section: Follicular Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, eight studies used dermoscopy [40][41][42][43][44][45][46][47] (of which two studies used polarized light 40,41 ), and one article used video dermoscopy for diagnostic and monitoring purposes. 48 ETR was the most studied rosacea subtype.…”
Section: Dermoscopymentioning
confidence: 99%